2012
DOI: 10.1007/s10725-011-9649-z
|View full text |Cite
|
Sign up to set email alerts
|

Gold-nanoparticle induced enhancement in growth and seed yield of Brassica juncea

Abstract: Experiments were carried out to determine the effect of Gold-nanoparticles on the growth profile and yield of Brassica juncea, under field conditions. Five different concentrations (0, 10, 25, 50 and 100 ppm) of Goldnanoparticles were applied through foliar spray. Presence of Gold-nanoparticles in the leaf tissues was confirmed through atomic absorption spectroscopy. Various growth and yield related parameters, including plant height, stem diameter, number of branches, number of pods, seed yield etc. were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(168 citation statements)
references
References 23 publications
9
157
1
1
Order By: Relevance
“…78 In addition to negative effects on chlorophyll biosynthesis, other NPs such as Au, TiO 2 , and ZnO were shown to enhance the chlorophyll content in mustard (Brassica juncea), cucumber, and clusterbean (Cyamopsis tetragonoloba L.), respectively. 59,79,80 Lipid peroxidation is another important parameter that is indicative of cell membrane integrity. ROS generation is known to be a primary factor that results in cell membrane damage through lipid peroxidation, leading to ion leakage and potential cell death.…”
Section: Biotransformation Of Metal-based Nps Inside Plantsmentioning
confidence: 99%
“…78 In addition to negative effects on chlorophyll biosynthesis, other NPs such as Au, TiO 2 , and ZnO were shown to enhance the chlorophyll content in mustard (Brassica juncea), cucumber, and clusterbean (Cyamopsis tetragonoloba L.), respectively. 59,79,80 Lipid peroxidation is another important parameter that is indicative of cell membrane integrity. ROS generation is known to be a primary factor that results in cell membrane damage through lipid peroxidation, leading to ion leakage and potential cell death.…”
Section: Biotransformation Of Metal-based Nps Inside Plantsmentioning
confidence: 99%
“…In addition, a marked increase was observed in the chlorophyll index, number of nodules, and crop yield. Arora et al (2012) reported that foliar spray of gold on Brassica juncea plant in field experiments showed positive effect as it resulted in increased plant height, stem diameter, number of branches, number of pods, and seed yield. Interestingly, gold nanoparticles also improved the redox status of treated plants.…”
Section: Nano-fertilizers and Plant Growthmentioning
confidence: 99%
“…The Au nanoparticles located in the nucleus and the applications of defamation suggested at both species are regarded as hyperaccumulators of Au nanoparticles [145147]. Additionally, it is documented that Au nanoparticle are transported inside the cells through plasmodesmata.…”
Section: Engineered Nanomaterials: On Plant Growthmentioning
confidence: 99%